Social relationships and GP use of middle-aged and older adults in Europe: a moderator analysis. Issue 4 (7th April 2018) - Bremer, Daniel; Lüdecke, Daniel; Vonneilich, Nico; von dem Knesebeck, Olaf
Abstract : Objectives: This paper investigates (1) how social relationships (SRs) relate to the frequency of general practitioner (GP) visits among middle-aged and older adults in Europe, (2) if SRs moderate the association between self-rated health and GP visits, and (3) how the associations vary regarding employment status. Methods: Data stem from the Survey of Health, Ageing and Retirement in Europe project (wave 4, 56 989 respondents, 50 years or older). GP use was assessed by frequency of contacts with GPs in the last 12 months. Predictors were self-rated health and structural (Social Integration Index (SII), social contact frequency) and functional (emotional closeness) aspects of SR. Regressions were used to measure the associations between GP use and those predictors. Sociodemographic and socioeconomic factors were used as covariates. Additional models were computed with interactions. Results: Analyses did not reveal significant associations of functional and structural aspects of SR with frequency of GP visits (SII: incidence rate ratio (IRR)=0.99, 95% CI 0.97 to 1.01, social contact frequency: IRR=1.04, 95% CI 1.00 to 1.07, emotional closeness: IRR=1.02, 95% CI 1.00 to 1.04). Moderator analyses showed that 'high social contact frequency people' with better health had more statistically significant GP visits than 'low social contact frequency people' with better health. Furthermore, people with poor health and an emotionally close network showed a significantly higher number of GP visits compared with people with same health, but less close networks. Three-way interaction analyses indicated employment status specific behavioural patterns with regard to SR and GP use, but coefficients were mostly not significant. All in all, the not employed groups showed a higher number of GP visits. Conclusions: Different indicators of SR showed statistically insignificantly associations with GP visits. Consequently, the relevance of SR may be rated rather low in quantitative terms for investigating GP use behaviour of middle-aged and older adults in Europe. Nevertheless, investigating the two-way and three-way interactions indicated potential inequalities in GP use due to different characteristics of SR accounting for health and employment status.